Postthoracotomy Ipsilateral Shoulder Pain: A Literature Review on Characteristics and Treatment - Fardin Yousefshahi; Oana Predescu; Melissa Colizza; Juan Francisco Asenjo (Pain Research and Management)
Context. Postthoracotomy Ipsilateral Shoulder Pain (IPS) is a common and sometimes intractable pain syndrome. IPS is different from chest wall pain in type, origin, and treatments. Various treatments are suggested or applied for it but none of them is regarded as popular accepted effective one. Objectives. To review data and collect all present experiences about postthoracotomy IPS and its management and suggest future research directions. Methods. Search in PubMed database and additional search for specific topics and review them to retrieve relevant articles as data source in a narrative review article. Results. Even in the presence of effective epidural analgesia, ISP is a common cause of severe postthoracotomy pain. The phrenic nerve has an important role in the physiopathology of postthoracotomy ISP. Different treatments have been applied or suggested. Controlling the afferent nociceptive signals conveyed by the phrenic nerve at various levels—from peripheral branches on the diaphragm to its entrance in the cervical spine—could be of therapeutic value. Despite potential concerns about safety, intrapleural or phrenic nerve blocks are tolerated well, at least in a selected group of patient. Conclusion. Further researches could be directed on selective sensory block and motor function preservation of the phrenic nerve. However, the safety and efficacy of temporary loss of phrenic nerve function and intrapleural local anesthetics should be assessed.